Measuring Poverty Using Both Income and Wealth - Zagorsky, Jay L. (Journal of Income Distribution®, 2005)
Since official U.S. poverty measures are based solely on income, the amount of wealth held by a family is immaterial in determining their poverty status. This research expands the poverty definition to encompass a family’s total financial resources. While most income-poor families have little or no wealth, approximately one-third have significant holdings. Using total financial resources both lowers average U.S. poverty rates over selected years from 15.2% of all families to a range between 8.8% and 11.3% and provides a measurement tool for tracking the effects of government wealth-building programs on families under the poverty line.